PERAN PEMERINTAH DALAM PERLINDUNGAN KONSUMEN TERHADAP PERNIAGAAN PAKAIAN BEKAS IMPOR PASCA BERLAKUNYA PERATURAN MENTERI PERDAGANGAN NOMOR 40 TAHUN 2022 - Mansyurin, Muhammad Roikhan; Rani Apriani (Universitas Kapuas, 2024)
This research aims to find out the legal protection of consumers on the trade in imported used clothing and the government's efforts in providing guidance and supervision of the trade in imported used clothing by business actors after the enactment of Regulation of the Minister of Trade Number 40 of 2022 concerning Amendments to Regulation of the Minister of Trade Number 18 of 2021 concerning Goods Prohibited from Export and Goods Prohibited from Import. The research method used in this research is normative juridical with secondary data in the form of laws and regulations, books, legal scientific works related to research. The results showed that after the enactment of Regulation of the Minister of Trade Number 40 of 2022, the government was increasingly assertive in taking action against smugglers of imported used clothing and business actors who traded in imported used clothing by closing shopping centres for imported used clothing which aimed to provide protection to consumers while still paying attention to the rights of business actors. The government has carried out its obligation to provide guidance and supervision of consumer protection as mandated in the consumer protection law.